Feature Tasawuf Ibn Arabi (Analysis of Sufistic Values in the Book of FuṠuṠ Al- Ḥikam) - Susanti, Listiawati; Amroeni, Amroeni; Nasution, Hasan Bakti (Budapest International Research and Critics University, 2019)
The aims of this study is to find out the sufistic values in book of FuṠuṠ Al- Ḥikam. This study used qualitative research. The result shows Ibn ‘Arabí̄ has nothing at all to carry the name and opinion of a philosopher or figure both Islamic and outside Islam in initiating his thinking. Even if he mentions the name or the name of one character in order to reject their opinion or compare it with the results obtained. For Fuṡuṡ al-Ḥikam Ibn ‘Arabí̄ to prove that the book was indeed given by the prophet directly to him.